Determination of Playing Related Postural Problems in Guitar Students - AKEL, BURCU SEMİN (My University, 2019)
Objective: A significant percentage (%37) of musicians suffer musculoskeletal disorders that are sufficiently serious to affect performance. A common risk factor for musculoskeletal disorders is a poor posture.ln this study, we aimed to determine of playing-related postural problems in guitar students. Materials and Methods: Nineteen guitar bachelor students participated. Demographic data were recorded and static and dynamic posture analysis were performed via observation and video recordings; which were analyzed by a physiotherapist, an occupationaltherapist and a guitarist. Awkward postures were recorded. Posture was evaluated both globally and for individual body regions. Overall posture was divided into 3 categories: rigid, slumped, physiological. Pain was assessed with The Musculoskeletal Pain Intensity and Interference Questionnaire for Musicians. Results: Most of the individuals (55%) experienced pain or problems that might hinder their playing skills in the last year.The most common locations of pain or problems were: shoulder, wrist, scapula and neck.The overall static posture was poor in 38% of participants when standing(33%rigid, 5% slumped). During playing, the posture was more often slumped than rigid(66%). The location of the gravity axis in the sagittal plane were forward-shifted(%55), however the physiological posture was maintained at the frontal plane.The most common problems encountered were shoulder imbalance (%61), rotation of the head(%77), rotation of body(%72), right wrist excessive ulnar deviation(%33) and thumb positioning(%72). Conclusions: According to the posture analysis, rotation and slumpy positioning was the main problem. This situation puts greater problems on the muscles of the back and abdomen and may effect proper breathing. The regions that have poor posture was neck, shou Ider, wrist and thumb. Considering this, we believe that educating music students in proper playing posture and postural awareness can be beneficial in decreasing performance-related postural problems.